Modification of Colocasia esculenta Starch with Acetylation Process - Dedin Finatsiyatull Rosida; Risha Yuliani; Sri Djajati (Future Science)
Modified starch is treated to change one or more physical or chemical properties. Modified starch is needed in food products to improve the texture of the paste, improve viscosity, and maintain starch granules at high temperatures. One chemical modification of starch is acetylation using acetic acid. Many tubers are not yet widely used, so they need to be developed through the change of acetylation-modified starches. Tubers (Colocasia esculenta) has a large enough starch content so that it has the potential to be processed and has high economic value. The purpose of this study was to determine the best treatment between the concentration of acetic acid and the soaking time in starch modification. This study used a completely randomized design factorial. The first factor was the concentration of acetic acid (4%, 6%, and 8%) and the second factor was the duration of soaking (30, 60, and 90 minutes). The best treatment was modified starch with 8% acetic acid and 90 minutes soaking time. This resulted to contained moisture of 5.97%, ash 1.39%, starch 63.49%, amylose 29.93%, swelling power 20.44 g / g, solubility 17.67%, yield 89.28%, substitution degree 0.66, viscosity 3589 cP.